2012
DOI: 10.3390/cells1020168
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy and Cell Responses Related to Mitochondrial Dysfunction, Lipid Metabolism and Unconventional Secretion of Proteins

Abstract: Macroautophagy has important physiological roles and its cytoprotective or detrimental function is compromised in various diseases such as many cancers and metabolic diseases. However, the importance of autophagy for cell responses has also been demonstrated in many other physiological and pathological situations. In this review, we discuss some of the recently discovered mechanisms involved in specific and unspecific autophagy related to mitochondrial dysfunction and organelle degradation, lipid metabolism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 172 publications
(282 reference statements)
0
9
0
Order By: Relevance
“…Lysosomes are essential for autophagy, and autophagic clearance of dysfunctional mitochondria represents an important element of mitochondrial quality control [ 15 ]. It is easy to speculate that lysosomal dysfunction such as in LSDs [ 16 ] leads to the abnormal accumulation of non-hydrolysed autophagy cargos such as mitochondria and other organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Lysosomes are essential for autophagy, and autophagic clearance of dysfunctional mitochondria represents an important element of mitochondrial quality control [ 15 ]. It is easy to speculate that lysosomal dysfunction such as in LSDs [ 16 ] leads to the abnormal accumulation of non-hydrolysed autophagy cargos such as mitochondria and other organelles.…”
Section: Introductionmentioning
confidence: 99%
“…A second mechanism allowing mobilization of FFAs is the macroautophagy of LDs (lipophagy), a process identified both in vitro and in vivo in rat RALA255-10G hepatocytes exposed to oil-rich medium and in liver-specific conditional autophagy-related 7 (Atg7) knock-out mice, respectively (Demine et al, 2012;Singh, Kaushik et al, 2009). In these conditions, the recruitment of light chain 3 (LC3), an autophagosomal marker, to the LD is observed, initiating the formation of autophagosomal engulfment of the LD in an Atg7-dependent manner and allowing the fusion with lysosomes in which lipolytic enzymes digest the TAG contained in LDs (Demine et al, 2012;Singh, Kaushik et al, 2009). So far, the existence of lipophagy has been confirmed in hepatocytes (Singh, Kaushik et al, 2009) (Martinez-Lopez et al, 2016), white (Lettieri Barbato, Tatulli, Aquilano, & Ciriolo, 2013) and brown (Martinez-Lopez et al, 2016) adipocytes, pancreatic β cells (Pearson et al, 2014), T cells (Hubbard et al, 2010), or neurons (Kaushik et al, 2011).…”
mentioning
confidence: 99%
“…This suggests that the reprogramming process may require the consumption of large amounts of lipid, which can provide metabolites or energy. Previous studies have identified a critical function for autophagy during lipid metabolism 24 25 , and this led us to further investigate the effects of Rab32 on autophagy during reprogramming.…”
Section: Resultsmentioning
confidence: 99%